Optimizing Healthcare Professionals' Communication with Patients during Inpatient Hospital Discharge: A Systematic Review - Gultom, Chiefriana Dearni; Basabih, Masyitoh (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2025)
This systematic review analyzed the role of communication between nurses, doctors, and patients in the inpatient discharge process, as well as the barriers encountered during this process. A total of 34 studies meeting the inclusion criteria—articles published in English or Indonesian addressing nurse-doctor communication and patient discharge—were analyzed. The exclusion criteria included studies that did not involve nurse-doctor communication, did not assess discharge communication, or did not undergo peer review. Findings from the studies indicate that caregiver involvement, the use of written guidelines, and communication technologies such as telemedicine can enhance patient understanding and improve discharge outcomes. However, barriers such as lack of coordination among medical professionals, communication difficulties with patients who have language limitations or complex medical conditions, and unclear post-discharge information were identified. This review adheres to the PRISMA reporting standards and is registered with PROSPERO. The study provides insights into the importance of clear communication, caregiver involvement, and interprofessional collaboration in improving patient safety and discharge success. It is hoped that these findings will help enhance the effectiveness and safety of patient discharge practices.